Wycena aktywów finansowych w świetle ustawy o rachunkowości oraz rozporządzenia Ministra Finansów - Krzeszowski, Wojciech Dawid (Financial Assets Valuation in the Light of the Accounting Act and the Finance Minister Ordinance, 2005)
A close look at the economy shows growing interest in financial instruments. The financial instruments are regulated in an array of legal acts. The following considerations are focused on the valuation of financial instruments that constitute corporate property, i.e. financial assets, in the light of the Accounting Act and the Finance Minister's ordinance.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 95-103